Comprehensive Analysis of the Expression and Prognosis Value of Chromobox Family Members in Clear Cell Renal Cell Carcinoma - Zhu, Yuanyuan; Pu, Zhangya; Li, Zhenfen; Lin, Ying; Li, Ning; Peng, Fang (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) accounts for 80% of all renal cancers and has a poor prognosis. Chromobox (CBX) family protein expression has been reported in a variety of human malignancies, but the roles of CBXs in ccRCC remain unclear. In this study, by using ONCOMINE, UALCAN, GEPIA, Kaplan-Meier Plotter, cBioPortal, and TIMER, we found the transcriptional levels of CBX3 and CBX4 in ccRCC tissues were significantly higher than those in normal kidney tissues, whereas the transcriptional levels of CBX1, CBX5, CBX6, and CBX7 were significantly reduced in ccRCC tissues. The promoters of CBX2, CBX3, CBX4, CBX5, CBX6, CBX7, and CBX8 were hypermethylated, whereas the CBX1 promoter was hypomethylated in ccRCC. The expression of CBX1, CBX3, CBX4, CBX5, CBX6, and CBX7 was significantly associated with clinicopathological parameters in ccRCC patients. ccRCC patients with high expression levels of CBX3, CBX4, and CBX8 and low expression levels of CBX1, CBX5, CBX6, and CBX7 showed a strong association with poor overall survival. Genetic alterations in CBXs were correlated with poor overall survival and disease-free survival in patients with ccRCC. Moreover, we found significant associations between the expression of CBXs and infiltration of immune cells (B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells). Our results provide novel insights into the development of CBX-based biomarkers and therapeutic targets for ccRCC.